(untitled) (Biological Sciences - PJSIR, 2010)
Fluoride, chloride and nitrate anions were determined in drinking water samples using techniques of ion selective electrodes (ISE) and non-suppressed/suppressed ion chromatography (IC). Detection limit, percentage recovery and run time were evaluated for the two methods. Detection limits for ISE [0.02, 0.20 and 1.7 ppm (?g/mL) for fluoride, chloride and nitrate, respectively], were better than those for non suppressed IC (2.0, 1.0 and 2.0 ppm for fluoride, chloride and nitrate, respectively). Suppressed IC was used to measure fluoride. Statistical analysis of the data revealed no evidence of systematic difference between ISE and non suppressed IC for chloride and nitrate. Fluoride concentrations in all water samples were lower, while chloride and nitrate concentrations in some samples were higher than the maximum contaminant levels established by the United States Environmental Protection Agency.